182k views
5 votes
Evaluate (You can use which ever first step you
selected above)

Evaluate (You can use which ever first step you selected above)-example-1

1 Answer

6 votes


(3 * 3 * 2^( - 4) * 2^(0) )/((3 * 2 ^( - 3)) ^(2) ) \\ = (3^( 1+1 ) * 2^( - 4 + 0) )/(3 * 2 ^( - 3 * 2) ) \\ = \frac{ {3}^(2) * {2}^( - 4) }{3 * {2}^( - 6) } \\ = 3^(2 - 1) * 2^( - 4 - ( - 6)) \\ = 3 * {2}^( - 4 + 6) \\ = 3 * {2}^(2) \\ = 3 * 4 \\ = 12

I USED THE LAWS OF EXPONENTS.

IF YOU DO NOT KNOW THEM PLEASE TELL ME AS SOON AS POSSIBLE TO ARRANGE FOR YOU.

User Ancy
by
5.6k points